2018
DOI: 10.1155/2018/5070742
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Profile of Different Clinical Isolates against Third-Generation Cephalosporins

Abstract: Background Drug resistant microorganisms lead to an increase in morbidity and mortality as they boost the risk of inappropriate therapy. Hence, data on antimicrobial resistance help define the best possible treatment for individual patients. Therefore, this study aimed to screen the antimicrobial resistant profile of 3rd generation cephalosporin drugs in Jimma University Specialized Teaching Hospital. Methods A hospital based prospective cross-sectional study was conducted in Jimma University Specialized Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
48
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 28 publications
16
48
4
Order By: Relevance
“…Our study showed that nearly 70% of isolates were ceftriaxone resistant. A similar nding was reported from Ethiopia [23] and 4 year consecutive study from Greece [18]. Cipro oxacin and o oxacin are alternative antibiotic of choice if the isolates are ESBL producers.…”
Section: Discussionsupporting
confidence: 81%
“…Our study showed that nearly 70% of isolates were ceftriaxone resistant. A similar nding was reported from Ethiopia [23] and 4 year consecutive study from Greece [18]. Cipro oxacin and o oxacin are alternative antibiotic of choice if the isolates are ESBL producers.…”
Section: Discussionsupporting
confidence: 81%
“…The resistance was lower than that in studies carried out in India, where the resistance of Klebsiella pneumoniae to gentamycin reached 80% in one study and 100% in another study. In the case of E. coli, the resistance ranged from 48.20% to 92.4% [31,32]. The WHO GASP statistics of several countries from 2009 to 2014 presented continual prevalent gonococcal resistance to azithromycin, but azithromycin was still effective against Shigella sp.…”
Section: Antibiotic Nonsusceptibilitymentioning
confidence: 99%
“…Elhadidy & Mohammed (2013) and Blanco et al (2004) reported the presence of serotypes O22, O120, O2, O141 O119, O34 and O49 from E. coli isolated from raw milk samples which is in agreement to the present study. Gashe et al (2018) reported 60% resistance against ceftazidime and 59% against ceftriaxone in a prior study. Xu et al (2018) reported 20% resistance against cefoxitin, Jena et al (2018) reported 61% resistance against aztreonem and 36% against cefpodoxime in theie studies.…”
Section: Polymerase Chain Reactionmentioning
confidence: 95%